B-Well-Posedness for Set Optimization Problems Involving Set Order Relations: Pham Thi Vui, Rabian Wangkeeree, Lam Quoc Anh - Team, Support (Thai Journal of Mathematics, 2018)
In this paper, both pointwise and global B-well-posedness for set op- timization problems involving three kinds of set order relations are investigated. Characterizations and sufficient and/or necessary conditions of these types of well- posedness are given. Moreover, pointwise L-well-posedness and relationships be- tween these kinds of pointwise well-posedness are studied.